Hedgehog transcriptional effector GLI mediates mTOR-Induced PD-L1 expression in gastric cancer organoids. (10th October 2021) - Koh, Vivien; Chakrabarti, Jayati; Torvund, Meaghan; Steele, Nina; Hawkins, Jennifer A.; Ito, Yoshiaki; Wang, Jiang; Helmrath, Michael A.; Merchant, Juanita L.; Ahmed, Syed A.; Shabbir, Asim; Yan So, Jimmy Bok; et al.
Abstract: Tumors evade immune surveillance by expressing Programmed Death-Ligand 1 (PD-L1), subsequently inhibiting CD8 + cytotoxic T lymphocyte function. Response of gastric cancer to immunotherapy is relatively low. Our laboratory has reported that Helicobacter pylori -induced PD-L1 expression within the gastric epithelium is mediated by the Hedgehog (Hh) signaling pathway. The PI3K/AKT/mTOR pathway is activated in gastric cancer and may have immunomodulatory potential. We hypothesize that Hh signaling mediates mTOR-induced PD-L1 expression. Patient-derived organoids (PDOs) were generated from gastric biopsies and resected tumor tissues. Autologous organoid/immune cell co-cultures were used to study the immunosuppressive function of MDSCs. NanoString Digital Spatial Profiling (DSP) of immune-related protein markers using FFPE slide-mounted tissues from gastric cancer patients was performed. DSP analysis showed infiltration of immunosuppressive MDSCs expressing Arg1, CD66b, VISTA and IDO1 within cancer tissues. Orthotopic transplantation of patient derived organoids (PDOs) resulted in the engraftment of organoids and the development of histology similar to that observed in the patient's tumor tissue. PDO/immune cell co-cultures revealed that PD-L1-expressing organoids were unresponsive to nivolumab in vitro in the presence of PMN-MDSCs. Depletion of PMN-MDSCs within these co-cultures sensitized the organoids to anti-PD-1/PD-L1-induced cancer cell death. Rapamycin decreased phosphorylated S6K, Gli2 and PD-L1 expression in PDO/immune cell co-cultures. Transcriptional regulation of PD-L1 by GLI1 and GLI2 was blocked by rapamycin. In conclusion, the PDO/immune cell co-cultures may be used to study immunosuppressive MDSC function within the gastric tumor microenvironment. The mTOR signaling pathway mediates GLI-induced PD-L1 expression in gastric cancer. Highlights: Myeloid derived suppressor cells (MDSCs) accumulate within the tumor microenvironment (TME) and may contribute to resistance to immunotherapy. The PI3K/AKT/mTOR pathway is activated in gastric cancer and may have immunomodulatory potential. An autologous cancer PDO/immune cell co-culture system may be used to investigate PD-L1/PD-1 blockade together with the inhibition of immunosuppressive cells MDSCs. The mTOR pathway mediates the non-canonical Hedgehog signaling cascade to induce PD-L1 expression. The mTOR signaling pathway may be targeted to decrease PD-L1 expression and increase response to immunotherapy in gastric cancer.